Imaging of Sports Ligamentous Injuries of the Elbow - Beltran, Luis S.; Bencardino, Jenny T.; Beltran, Javier (Seminars in Musculoskeletal Radiology, 2013)
Ligamentous injuries of the elbow are common in sports. The diagnosis is usually based on a combination of the assessment of the mechanism of injury during the sporting activity and physical examination. Imaging with radiographs and MR imaging has an important diagnostic role, particularly when the clinical presentation is unclear and to evaluate for other important potential associated injuries such as myotendinous injuries, fractures, dislocations, and osteochondral lesions. Treatment includes conservative and surgical measures depending on the severity of the instability and associated injuries. We provide a detailed review of sports-related injuries of the medial and lateral collateral ligament complexes of the elbow with an emphasis on imaging manifestations of disease and a discussion of the anatomy, biomechanics, and treatment options.
Keywords: ligament injuries; sports ligamentous injuries; elbow